The Game Maker’s Apprentice: Game Development for Beginners - Habgood, Jacob (Apress, 2013)
This book provides a collection of engaging tutorials that introduce you to the Game Maker tool and teach you how to use it. The first four parts of the book take you step by step through seven different projects using Game Maker’s simple drag-and-drop programming system. By the time you’ve finished making Evil Clutches, Galactic Mail, Lazarus, Super Rainbow Reef, Koalabr8, Wingman Sam, and Tank War, you’ll have a well-rounded experience of making games with Game Maker. Parts 2, 3, and 4 also end with game design chapters that encourage you to stand back from your creations and consider how principles of game design can be used to make them more fun. Moreover, we don’t just talk about it, but we provide new versions of the games with improved features so that you can experience for yourself how solid game design can lead to good gameplay.